Epidemiology, species distribution, antifungal susceptibility, and outcome of candidemia in intensive care units in Isfahan, Iran - Azam Haghighatfard; Saeed Abbasi; Pegah Alijani; Farzaneh Afyooni Akbari; Hossein Rashidi; Parvin Dehghan (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Candidemia is known as an invasive fungal infection with high mortality. The prevalence of candidemia in intensive care unit (ICU) patients is more than in other hospital wards. Early diagnosis of candidemia in these patients is essential for disease management.Materials and Methods: This study included 250 patients suspected of candidemia. Blood samples were taken from patients and incubated. The fungal isolates were identified by PCR-RFLP method using MSP I restriction enzyme. Demographic characteristics, risk factors, underlying diseases, and laboratory analysis results were mined in this study.Results: In total, 22 blood samples were identified as positive for Candida yeasts in culture. The most common underlying diseases in these patients were heart disease and hypertension (36.4%). Candida albicans with 12 cases (54.5%) was the most isolated species, followed by C. parapsilosis (n=5, 22.7%), C. glabrata (n=4, 18.2%), and C. tropicalis (n=1, 4.5%) in descending order. Intravenous catheter use was recognized as the most common risk factor in patients with candidemia (77.3%), and after that, the use of mechanical ventilation (68.2%) and urinary catheter (40.9%) obtained the highest frequency. Furthermore, 17 patients were prescribed at least one antifungal drug, of which fluconazole was the most used (36.4%). The mortality rate in patients in this study was 63.6%. All C. albicans isolates were susceptible to antifungal agents but in nonalbicans Candida (NAC), drug resistance to fluconazole, voriconazole, and caspofungin were observed.Conclusion: Although C. albicans was the most common fungal species in this study, the prevalence of NAC species was high. The increasing frequency of NAC species is a concern because they have different patterns of drug resistance. Recognition of risk factors in patients admitted to ICUs can help prevent candidemia or properly manage the disease.